2019
DOI: 10.1111/adb.12851
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin in the lateral septum decreases conditioned place preference to amphetamine and nucleus accumbens dopamine release

Abstract: The lateral septum (LS) is a limbic nucleus interconnected with several brain areas involved in the regulation of mood and reward. Vasopressin (AVP) is a neuropeptide that has been related to the effects of drugs of abuse, but its role in the addictive process is poorly understood. LS expresses a high density of AVP 1A receptors (V 1A). The aim of this work was to examine whether the modulation of LS AVP system affects the behavioral and neurochemical responses to amphetamine (AMPH) in male rats. Our results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 54 publications
1
12
0
1
Order By: Relevance
“…The lateral septum (LS) is a part of the limbic and reward system which sends afferent and efferent projections to many subcortical and cortical brain areas including the ventral tegmental area, amygdala, bed nucleus of stria terminalis, nucleus accumbens, hippocampus, prefrontal cortex, etc. It is suggested that LS is involved in the formation of wide class of addictions and for instance AUD (Deng et al, 2019;Gárate-Pérez et al, 2021). In the current model of addiction, cycle the role of LS has not been determined unequivocally, implying that LS participates in formation of associations between alcohol and contextual stimuli, goalmotivated behaviour and its shift to habit that is observed in addiction, regulation of stress response, memory and emotion development.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The lateral septum (LS) is a part of the limbic and reward system which sends afferent and efferent projections to many subcortical and cortical brain areas including the ventral tegmental area, amygdala, bed nucleus of stria terminalis, nucleus accumbens, hippocampus, prefrontal cortex, etc. It is suggested that LS is involved in the formation of wide class of addictions and for instance AUD (Deng et al, 2019;Gárate-Pérez et al, 2021). In the current model of addiction, cycle the role of LS has not been determined unequivocally, implying that LS participates in formation of associations between alcohol and contextual stimuli, goalmotivated behaviour and its shift to habit that is observed in addiction, regulation of stress response, memory and emotion development.…”
Section: Introductionmentioning
confidence: 74%
“…In the current model of addiction, cycle the role of LS has not been determined unequivocally, implying that LS participates in formation of associations between alcohol and contextual stimuli, goalmotivated behaviour and its shift to habit that is observed in addiction, regulation of stress response, memory and emotion development. Manipulations with LS changed the course of addiction eliminating the rein-forcing action of alcohol (Jonsson et al, 2017), blocking conditional place preference for different substance of abuse (Sartor & Aston-Jones, 2012;Gárate-Pérez et al, 2021), attenuating intake and preference of alcohol (Ryabinin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Supporting these findings, a decrease of AVP content has been observed in the hypothalamus after 4 days of cocaine treatment, suggesting that the increase in AVP release at the hypothalamic level is followed by a depletion of this neuropeptide content in this region [ 82 ]. Recent studies from our laboratory showed that amphetamine (AMPH) induced conditioned place preference (CPP) and produced a decrease in AVP content in the LS nucleus, which is interconnected with areas linked to the regulation of mood and reward [ 83 , 84 ]. Moreover, the chronic administration of opiates (e.g., morphine) has been shown to differentially alter OT expression in various brain areas, including a decrease of OT in SON and NAc, and an increase in VTA [ 85 ].…”
Section: Neuropsychiatric Conditions: Ot and Avp Rolementioning
confidence: 99%
“…Indeed, AVP-deficient animals did not develop cocaine sensitization, suggesting that AVP could participate in the addiction process [ 101 ]. Contrary to this evidence, our group recently demonstrated that the microinjection of AVP in LS impairs the expression of AMPH-induced CPP and that this effect is mediated by the activation of the V 1A R in the LS, which could produce the inhibition of GABAergic projections to the VTA, increasing the inhibitory tone in this nucleus, and therefore inducing a decrease in the dopaminergic activity at the NAc [ 84 ]. Moreover, animal studies suggest that the blockade of V 1B R (but not V 1A R) decreases the high level of intake in dependent animals and diminishes the emotional response to a stressor during withdrawal for cocaine [ 86 ].…”
Section: Neuropsychiatric Conditions: Ot and Avp Rolementioning
confidence: 99%
“…LS має зв'язки з усіма ключовими структурами, задіяними в формуванні залежності. За останні роки з'явилася низка робіт, які доводять участь септальної ділянки у розвитку залежності, особливо в контексті встановлення асоціативних зв'язків між алкоголем і тригерними стимулами [6,8,12,15,28,33].…”
Section: вступunclassified